Skincare Lokal di Era Digital: Analisis Pengaruh Aktifitas Media Sosial Terhadap Ekuitas Merek dan Respon Pelanggan - Adinda Dwita Kartika; Raden Roro Ratna Roostika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The practice of skincare, commonly known as skincare, is not a new phenomenon. The growing interest in skincare has created new opportunities in the business world, leading to increased competition among skincare companies. This research aims to examine and analyze the impact of social media marketing activities on brand equity and customer response to local skincare products in Indonesia. The study was conducted nationwide to focus on the local skincare product market and users in Indonesia. The research involved 224 respondents who participated in an online survey for easy questionnaire distribution. The data from the respondents were then processed using AMOS version 24. The research employed a quantitative approach with primary data collected through questionnaire distribution. The variables used in this study include social media marketing activities, brand awareness, brand image, electronic word of mouth, and commitment. Based on the research results, it is evident that social media marketing activities have a positive impact on brand awareness and brand image. Brand awareness does not significantly influence e-WOM, but brand image has a positive impact on e-WOM. Brand awareness has a positive influence on commitment, while brand image does not have a significant impact on commitment.